The effects of global budget on cost control and readmission in rural China: a difference-in-difference analysis. (2nd September 2017) - He, Ruibo; Miao, Yudong; Ye, Ting; Zhang, Yan; Tang, Wenxi; Li, Zhong; Zhang, Liang
Abstract: Background: Global budget (GB) is considered one of the most important payment methods available. Since a new round of healthcare system reforms in 2009, the Chinese government has been paying attention to this prospective payment. However, it is unclear whether GB has influenced cost control and how it works in rural China. Methods: YC county was chosen as the intervention group, with 33, 175 inpatients before and 36, 883 inpatients after the reform (2012 and 2014, respectively). ZJ county acted as the control group, with 23, 668 and 29, 555 inpatients, respectively. The inpatients' information was collected from a local insurance agency. The difference-in-difference method (controlling for age, gender, living status, severity of the disease, whether the patient had surgery, the level of medical institutions, and the secular trends of the two groups) was applied to estimate the effects on total spending (TS), reimbursement expense (RE), out-of-pocket payment (OOP), readmission rate, and seven kinds of medical service items. Results: At per practice level, the GB was associated with a ¥263.35 ( p  < .001) and ¥447.46 ( p  < .001) decrease in growth of TS and RE, respectively, while OOP increased by ¥188.06 ( p  < .001). At per capital level, the decrease in growth of TS and RE was ¥64.39 ( p  = .301) and ¥467.45 ( p  < .001), respectively, whereas the increase of OOP was more significant at ¥408.19 ( p  < .001). Savings were concentrated in unclassified items (¥197.68, p  < .001), drug prescription (¥69.03, p  < .001), surgery (¥40.18, p  < .001), cure (¥4.95, p  = .565), and diagnosis (¥3.61, p  = .064). Meanwhile, the readmission rate increased by 11.4% ( p  < .001). Conclusions: The GB has a prominent impact on curbing the growth of insurance fund expenditures, as well as drug and medical consumable costs. However, the patients' out-of-pocket payment has risen. Doctors decomposed hospitalization to deal with supervision, which was harmful to patients. Any medical insurance payment reform should be undertaken prudently, and its likely outcomes should be weighed comprehensively.